Determinant Factors Related To Covid-19 Prevention Behavior In Students At State Vocational School 3 Palembang - Eva Susanti; Yulisa Tri Hasanah (CV. AFDIFAL MAJU BERKAH, 2022)
COVID-19 prevention behavior is the main factor to break the chain of the spread of the COVID-19 disease. Behavioral determinants really determine students in implementing preventive measures against COVID-19. The purpose of this study was to determine the determinants of COVID-19 prevention behavior in students at State Vocational School 3 Palembang. This type of research is a quantitative research with a cross sectional research design. The population in this study were all students of State Vocational School 3 Palembang with the number of respondents 361 students, with a minimum sample size of 342. Data collection in this study was carried out using online and offline. The sampling method used is simple random sampling technique. Data analysis used Chi- square statistical test and logistic regression. The results of this study found a significant relationship between gender, knowledge, and attitudes towards COVID-19 prevention behavior in students at State Vocational School 3 Palembang. While the most dominant variable is attitude.